(untitled) (World Journal of Current Medical and Pharmaceutical Research, 2019)
The first trimester is the most critical stage of development during which the rudiments of all the major organ systems appear. The second trimester is characterized by the nearly complete development of organ systems. The third trimester represents a period of rapid fetal growth. The risks related to pregnancy in those over 35 years, old, especially primiparity. The higher rates of fertility (age specific fertility rate) were seen in women from 25-29 years or from 30-34 years29. Women are still considered to be the sole responsible for pregnancy, while men continue being absolved or omitted from their participation in the reproductive even. One of the most common risk factors for a high risk pregnancy is the age of the mother. Women with age under 17 or over 35 are at greater risk of complications than those between their late teens and early 30s35. It is advantageous to diagnosis the pregnancy as promptly as possible when a sexually active woman misses a menstrual period or has symptoms suggestively of pregnancy. In the event of Desired Pregnancy, prenatal care can begin early and potentially harmful medications and activities such as drug and alcohol use, smoking and occupational chemical exposed can be halted.